Reconciling subjects and contexts: the case for a pragmatic primary curriculum - John Smith (Educational Futures, 2008)
In this paper the author examines changes in the primary curriculum in this country since the time of the Plowden Report of 1967. Since that time there have been several changes of emphasis from teaching through subjects to teaching through contexts. The author considers some of the reasons for this oscillation and suggests some principles which a renewed primary curriculum might be constructed upon. The author also suggests that a renewed curriculum should place much greater emphasis upon the use of spoken language in the classroom and that much more consideration needs to be given to the challenges which change curriculum change poses for practitioners. For a number of reasons, it is suggested that the term ‘pragmatic’ might be a good label for the curriculum of the future.